(untitled) (Research, Society and Development, 2020)
The aim of this estudy was to estimate the prevalence of lack of functional denttion and associated factors among adults. A cross-sectional study was conducted on a random sample of 532 subjects aged between 20 and 59 in Patos, PB, in the Northeastern Brazil. The proportion of lack of functional dentition (< 21 natural teeth) was the outcome investigated. The independent variables were as follows: sociodemographic characteristics, use of dental services and behavioral aspects in health. Crude and adjusted prevalence ratios were estimated using a Poisson regression model. The prevalence of lack of functional dentition was 23,9%. The lack of functional dentition was strongly associated with age group, schooling level, smoking status and flossing. Social class and frequency of toothbrushing also they were associated to the investigation outcome. In conclusion, various factors were associated with the lack of functional dentition in adults emphasizing its importance as an oral health indicator.